Characterizing Aircraft Exhaust Emissions and Impact Factors at Tianjin Binhai International Airport via Open-Path Fourier-Transform Infrared Spectrometer - Jingbo Zhao; Zixiang Mao; Bo Han; Zhiyong Fan; Simeng Ma; Jingxin Li; Rui Wang; Jian Yu (Toxics)
The growth of the civil aviation industry has raised concerns about the impact of airport emissions on human health and the environment. The aim of this study was to quantify the emissions of sulfur dioxide (SO2), nitrogen oxides (NOX), and carbon monoxide (CO) from in-service aircraft via open-path Fourier-transform infrared (OP-FTIR) spectroscopy at Tianjin Binhai International Airport. The results suggest that the CO and NOX emission indices (EIs) for five common aircraft/engine combinations exhibited substantial discrepancies from those reported in the International Civil Aviation Organization (ICAO) databank. Notably, during the idling, approach, and take-off phases, the CO EIs exceeded the ICAO’s standard values by (11.04 ± 10.34)%, (56.37 ± 18.54)%, and roughly 2–5 times, respectively. By contrast, the NOX EIs were below the standard values by (39.15 ± 5.80)%, (13.57 ± 3.67)%, and (21.22 ± 4.03)% in the same phases, respectively. The CO and NOX EIs increased by 31–41% and decreased by 23–24%, respectively, as the ambient temperature decreased from −3 °C to −13 °C. This was attributed to lower temperatures reducing fuel evaporation, leading to inefficient combustion and increased CO emissions and lowering the combustion temperature and pressure, resulting in reduced NOX emissions. The CO EIs had a positive correlation with humidity (adjusted R2: 0.715–0.837), while the NOX EIs were negatively correlated with humidity (adjusted R2: 0.758–0.859). This study’s findings indicate that humidity is a crucial factor impacting aircraft exhaust emissions. Overall, this research will contribute to the development of scientifically informed emission standards and enhanced environmental management practices in the aviation sector.